Changes In Economic Conditions Of Irrigated Rice Field Farmers After The Pandemic In Karang Tengah Village Buay Madang Timur District OKU Timur Regency: Perubahan Kondisi Ekonomi Petani Padi Sawah Irigasi Pasca Pandemi di Desa Karang Tengah Kecamatan Buay Madang Timur Kabupaten OKU Timur - Ayu Ramadhani, Destiana Nur; Aryani, Desi; huanza, M (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2024)
The aims of this research are (1) Analyzing changes in the economic conditions of irrigated rice field farmers during and after the Covid-19 pandemic in Karang Tengah Village , (2) Analyzing the feasibility of farming irrigated rice farmers during and after the Covid-19 pandemic in Karang Tengah Village. The research results showed that there were significant changes in the economic conditions of rice field farmers during and after the Covid-19 pandemic in Karang Tengah Village, which occurred in production costs which increased by 20.83 percent after the Covid-19 pandemic. Household income increased by 36.71 percent after the Covid-19 pandemic. Farmer household consumption expenditure increased by 27.38 percent per year after the pandemic compared to during the Covid-19 pandemic. The area of cultivated land and the total allocation of working time in rice farming during and after the Covid-19 pandemic did not experience significant changes. The feasibility of farming carried out by irrigated rice field farmers during and after the Covid-19 pandemic in Karang Tengah Village is feasible. Keywords: Covid-19, changes in economic conditions, feasibility of farming